Comparative Analysis of Bread Properties Using Germinated and Un-Germinated Chickpea Flour - Gautam, Navin; Subedi, Ashma; Panta, Om Prakash (NPRC Journal of Multidisciplinary Research, 2025)
The aim of this study was to prepare and compare bread from refined wheat flour (RWF), germinated chickpea flour (GCF) and un-germinated chickpea flour (UGCF). The proximate composition of the flours was analyzed, and bread recipes were formulated using Design Expert software. Bread was prepared with varying proportions of refined wheat flour and UGCF. A (RWF: UGCF = 96.8:3.2), B (RWF: UGCF = 93.6:6.4), C (RWF: UGCF = 90.6:9.4), D (RWF: UGCF = 87.2:12.8), E (RWF: UGCF = 81.4:18.6), F (RWF: UGCF = 78.2:21.8), G (RWF: UGCF = 75:25), and H (RWF: UGCF = 100:0). The straight dough method was employed to prepare the bread. All variations showed significant differences (p<0.05) in loaf volume, weight, and specific volume compared to the control. Sensory evaluation was conducted for all eight formulations to assess acceptability, formulation D receiving the highest mean sensory scores across all attributes. The recipe for formulation D was subsequently used to prepare bread incorporating both RWF and GCF and found moisture content, crude protein, crude fat, crude fiber, ash, carbohydrate, iron, calcium, phytate and tannin were found as 42.63%, 14.95%, 6.98%, 1.01%, 0.84%, 773.75%, 2.73mg, 43.64mg, 153.97mg and 11.49mg respectively. No significant differences (p>0.05) were found between bread made with GCF and UGCF regarding ash content, carbohydrate, iron, and calcium. Significant differences (p<0.05) were observed in moisture content, crude protein, fat, fiber, phytate, and tannin content between the two types of bread.